2014
DOI: 10.1002/2013gl058888
|View full text |Cite
|
Sign up to set email alerts
|

Major role of the equatorial current system in setting oxygen levels in the eastern tropical Atlantic Ocean: A high-resolution model study

Abstract: Understanding the causes of the observed expansion of tropical ocean's oxygen minimum zones (OMZs) is hampered by large biases in the representation of oxygen distribution in climate models, pointing to incorrectly represented mechanisms. Here we assess the oxygen budget in a global biogeochemical circulation model, focusing on the Atlantic Ocean. While a coarse (0.5°) configuration displays the common bias of too large and too intense OMZs, the oxygen concentration in an eddying (0.1°) configuration is higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 31 publications
9
78
0
1
Order By: Relevance
“…The increase in the resolution of ocean circulation models improves the tropical circulation and associated oxygen distribution in the Atlantic (Duteil et al, 2014) and Pacific OMZs (Montes et al, 2014), suggesting that deficiencies in model physics largely contribute to the oxygen bias in coarser-resolution models. However, particularly the intermediate circulation (below 250 m) is still underestimated by these high-resolution simulations in realistic settings.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The increase in the resolution of ocean circulation models improves the tropical circulation and associated oxygen distribution in the Atlantic (Duteil et al, 2014) and Pacific OMZs (Montes et al, 2014), suggesting that deficiencies in model physics largely contribute to the oxygen bias in coarser-resolution models. However, particularly the intermediate circulation (below 250 m) is still underestimated by these high-resolution simulations in realistic settings.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Negatively biased model [O 2 ] is widespread in the tropics, where the model oxygen minimum zones (OMZs) are too extensive [ Moore et al , ]. This bias is common in coarse‐resolution ocean GCMs and is partially attributable to sluggish circulation yielding weak ventilation [ Brandt et al , , ; Dietze and Loeptien , ; Getzlaff and Dietze , ; Duteil et al , ]. The extent of OMZs is also sensitive to the prescribed remineralization profile for sinking organic matter, as well as the stoichiometric ratios used for growth and remineralization of organic matter [ Devries and Deutsch , ].…”
Section: Models and Numerical Experimentsmentioning
confidence: 99%
“…The NEUC is reproduced somewhat further south than observed, connecting at 2°N with the North Intermediate CounterCurrent, a link that does not seem to occur in the real ocean [ Brandt et al ., ]. These issues are likely due to the limited horizontal resolution of ECCO2, as high resolution appears necessary to properly model the intermediate‐depth equatorial circulation [ Duteil et al ., ]. Nevertheless, the Lagrangian pathways (Figure ) have revealed that the lCW of the naOMZ is only weakly linked to this equatorial region so we expect that the significance of these differences is likely small.…”
Section: The Upper Thermocline Circulation In the Ecco2 Modelmentioning
confidence: 99%